Topography and Dynamics of Co-author Networks - Micsinai, István (Szociológiai Szemle, 2023)
Co-author networks have become the center of the attention of both scientometrics and network researches during the last decade. In this article I put more emphasis on the scientometrics side, I compare the actual and the international results related to my topic.The outcome of the research is that the rate of co-authorship of the last fifty years in Hungary has no significant change. The number of the largest component of all publishing scientists in co-authorship covers only twenty-eight, thirty-three percent. The international co-operation shows surprisingly low number of articles and the distribution is uneven. The growth of networks - contrary to the ‘mature’ Western science - can be modeled easily by the logistic growth function.